Extended letrozole regimen versus clomiphene citrate for superovulation in patients with unexplained infertility undergoing intrauterine insemination: A randomized controlled trial - Sayed Ahmed M; Fouda Usama M (BMC, 2011)
Abstract Background The aim of this randomized controlled trial was to compare the efficacy of extended letrozole regimen with clomiphene citrate in women with unexplained infertility undergoing superovulation and intrauterine insemination (IUI). Methods Two hundred and fourteen patients with unexplained infertility were randomized into two equal groups using computer generated list and were treated by either letrozole 2.5 mg/day from cycle day 1 to 9 (extended letrozole group, 211 cycles) or clomiphene citrate 100 mg/day from cycle day 3 to 7 (clomiphene citrate group,210 cycles). Intrauterine insemination was performed 36 to 40 hours after HCG administration. Results Both groups were comparable with regard to number of mature follicles (2.24 +/- 0.80 Vs 2.13 +/- 0.76) and the day of HCG administration. Serum estradiol was significantly greater in clomiphene citrate group (356 +/- 151 Vs 822 +/- 302 pg/ml, P = < 0.001) and the endometrial thickness was significantly greater in extended letrozole group (9.10 +/- 1.84 Vs 8.18 +/- 1.93 mm, P = < 0.001).The pregnancy rate per cycle and cumulative pregnancy rate were significantly greater in extended letrozole group (18.96% Vs 11.43% and 37.73% Vs 22.86%, respectively). Conclusion The extended letrozole regimen had a superior efficacy as compared with clomiphene citrate in patients of unexplained infertility undergoing superovulation and IUI. Trial registration ClinicalTrials.gov, NCT01232075